Nitrogenous compounds balance and microbial protein synthesis in steers supplemented with sunflower crushed in partial replacement of soybean meal - doi: 10.4025/actascianimsci.v35i3.18654 (Acta Scientiarum. Animal Sciences, 2013)
Four steers in individual paddocks with Marandu grass (B. Brizantha) in 4x4 square designwere used to evaluate sunflower crushed supplementation in pasture-grazing animals on nitrogen balanceand microbial protein synthesis. Supplements at 6 g kg-1 body weight comprised corn, soybean meal, andmineral and soybean meal substituted at proportions 0, 20, 40 and 60%. Diet contained averages 6.79, 6.96,7.10 and 6.87% nitrogen respectively for substitution levels 0, 20, 40 and 60%. The inclusion of sunflowercrushed (SC) increased nitrogen intake and fecal excretion of nitrogen while providing a positive balance.Animals’ plasma urea concentration supplemented with SC was 28.13% lower than that of supplementedanimals without SC. SC inclusion did not change allantoin concentration, purine derivatives, microbialnitrogen, crude microbial protein and microbial efficiency microbial, with mean rates totaling 150.98 mmolday-1; 158.06 mmol day-1, 112.35 g day-1, 702.18 g day-1; 146.41 crude protein (CP) microbial kg-1 of TDN.Partial replacement of soybean meal by sunflower crushed improves nitrogen balance without alteringmicrobial protein synthesis and excretion of urea and creatinine